2022
DOI: 10.1039/d2nj00092j
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional nano-framework CoP/Co2P/Co3O4 heterojunction as a trifunctional electrocatalyst for metal–air battery and water splitting

Abstract: Clean renewable energy conversion and storage technologies, such as metal-air batteries, water splitting and fuel cells, require development of cost-effective trifunctional electrocatalyst toward oxygen reduction reaction (ORR), oxygen evolution reaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…4a and d) are positioned at potentials in the order HPBE > Pt/C > BE, an indication of the order of their corresponding ORR performance. 39,40 Their linear sweep voltammograms (Fig. 4b and e) corroborate this order.…”
Section: Resultssupporting
confidence: 60%
“…4a and d) are positioned at potentials in the order HPBE > Pt/C > BE, an indication of the order of their corresponding ORR performance. 39,40 Their linear sweep voltammograms (Fig. 4b and e) corroborate this order.…”
Section: Resultssupporting
confidence: 60%
“…As shown in Figure b, there was the smallest Tafel slope (108.5 mV dec –1 ) for the Co@N-CNT electrode and the Tafel slope of the core–shell Co@Co 3 O 4 @ N-CNT was smaller than the hollow Co 3 O 4 @N-CNT, which demonstrated that the Co@Co 3 O 4 @ N-CNT with a unique core–shell structure and abundant oxygen vacancies exhibited more enhanced reaction kinetics and higher transfer coefficient than the Co 3 O 4 @N-CNT. Contrasting to the properties of some other reported Co-based catalysts, Co@N-CNT and Co@Co 3 O 4 @ N-CNT require a lower overpotential to drive a current density of 10 mA cm –2 and a superior Tafel slope (Figure c). Moreover, the catalytic activity of the electrode is strongly influenced by the active sites and the electrochemically active surface area could be represented by measuring the double-layer capacitance ( C dl ) in the non-Faradic region at selected scan rates. As shown in Figure d, the C dl value of Co@Co 3 O 4 @N-CNT was significantly higher than that of Co 3 O 4 @N-CNT, illustrating the higher HER activity intuitively.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, H 2 is primarily produced industrially through the conversion of natural gas, steam and coal, which inevitably releases greenhouse gases. Amongst the various methods of hydrogen production, water splitting is considered an ideal high purity way to produce hydrogen and driven by the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) processes, which is important for global clean energy deployment and ecological protection [5][6][7][8][9][10][11]. The development of low−cost, stable and high−performance electrocatalysts is key to advancing the technology [12][13][14].…”
Section: Introductionmentioning
confidence: 99%